Serum AMH level to predict the hyper response in women with PCOS and non-PCOS undergoing controlled ovarian stimulation in art - Radha Vembu; Nellepalli Sanjeeva Reddy (Wolters Kluwer Medknow Publications, 2017)
Background: It is essential to determine the cut-off value of serum anti-Mullerian hormone (AMH) to predict the hyper response in assisted reproductive technology (ART). There are few studies mentioning the cut-off value for the hyper response in infertile women but not specifically for polycystic ovary syndrome (PCOS) and non-PCOS groups. With this in background, this study was conducted. Aim: To determine the cut-off value of serum AMH to predict the hyper response in women with PCOS and non-PCOS undergoing a controlled ovarian stimulation (COS) in ART. Objective: To compare the outcome of stimulation in PCOS and non-PCOS groups. Materials and Methods: All 246 women enrolled for Intra Cytoplasmic Sperm Injection (ICSI) fulfilling the selection criteria were recruited. On the day 3 of the cycle, the serum AMH, Follicle Stimulating Hormone (FSH), Luteinizing Hormone (LH), estradiol and antral follicle count (AFC) were measured. They underwent COS as per the unit protocol. They were divided into PCOS and non-PCOS groups as per the Rotterdam's criteria. The mean age, duration of infertility, Body Mass Index (BMI), Ovarian reserve markers and outcome of stimulation were compared. Using the Statistical Package for the Social Sciences version 16.0 software, the significant difference was measured by multivariate analysis, as well as a one-way analysis of variance with Tukey's post-hoc test was used. Results: Among 246 women, 31.3% were in PCOS group, and 68.7% were in non-PCOS group. Comparison of PCOS and non-PCOS groups showed a significant difference in the age with the mean age being 29.2 and 31.5 years, respectively. The mean AMH and AFC were 2-fold higher in PCOS group. The mean number of follicles, oocytes retrieved, MII and oocytes fertilised were significantly higher in PCOS group. The pregnancy rate was 52.6% in PCOS and 30.9% in non-PCOS group. In the PCOS group, 22.1% had ovarian hyper stimulation syndrome (OHSS), and only 4.7% had OHSS in non-PCOS group (P = 0.0005). Receiving Operator Curve (ROC) curve was plotted to predict the hyper response, which showed a cut-off value of 6.85 ng/ml with a sensitivity of 66.7% and a specificity of 68.7% for PCOS group and 4.85 ng/ml with a sensitivity of 85.7% and a specificity of 89.7% in non-PCOS group. Conclusion: The cut-off value of serum AMH to predict the hyper response in PCOS group is 6.85 ng/ml and in non-PCOS group is 4.85 ng/ml.